Telaah Sanad Hadis Tentang Kedudukan Akhlak Yang Luhur Pada Pembahasan Karakter Ulul Ilmi Dalam Buku Wahdatul Ulum Paradigma Pengembangan Keilmuan Dan Karakter Lulusan UIN Sumatera Utara - Bukhori, Al (UIN Sumatera Utara Medan, 2023)
Wahdatul Ulum is a scientific development paradigm at UIN North Sumatra, as explained in the book Wahdatul Ulum Paradigm of Scientific Development and Characteristics of Graduates of UIN North Sumatra which formulates Ulul Ilmi as the profile and character of its graduates. In terms of curriculum development, Al-Quran and Hadith will be positioned as the main references, and this information indicates that the discipline of Hadith plays an important role in the formation of Ulul Ilmi's character in the formulation of the Wahdatul Ulum paradigm. However, in explaining Ulul Ilmi's character regarding the position of noble morality in the sixth character of the nine characters, he cites a Hadith which is considered problematic in its sanad according to Nashruddin al-Albani narrated by Ibn Majah and Thabrani. Therefore it is necessary to study these problems in order to find out how the paradigm of Wahdatul Ulum UIN North Sumatra in the use of Hadith Science for its position as the shaper of Ulul Ilmi's character and how the position of the status of the Sanad Hadith is considered problematic, the authors try to study it through the library research method using the Naqd al-Sanad method and relevant methods, the study focused on the history of Ibn Majah, and it was concluded that the sanad of Ibn Majah's history is dhaif, due to the existence of several narrators in the sanad with majhul status whose quality and dhabi cannot be identified properly.Wahdatul Ulum is a scientific development paradigm at UIN North Sumatra, as explained in the book Wahdatul Ulum Paradigm of Scientific Development and Characteristics of Graduates of UIN North Sumatra which formulates Ulul Ilmi as the profile and character of its graduates. In terms of curriculum development, Al-Quran and Hadith will be positioned as the main references, and this information indicates that the discipline of Hadith plays an important role in the formation of Ulul Ilmi's character in the formulation of the Wahdatul Ulum paradigm. However, in explaining Ulul Ilmi's character regarding the position of noble morality in the sixth character of the nine characters, he cites a Hadith which is considered problematic in its sanad according to Nashruddin al-Albani narrated by Ibn Majah and Thabrani. Therefore it is necessary to study these problems in order to find out how the paradigm of Wahdatul Ulum UIN North Sumatra in the use of Hadith Science for its position as the shaper of Ulul Ilmi's character and how the position of the status of the Sanad Hadith is considered problematic, the authors try to study it through the library research method using the Naqd al-Sanad method and relevant methods, the study focused on the history of Ibn Majah, and it was concluded that the sanad of Ibn Majah's history is dhaif, due to the existence of several narrators in the sanad with majhul status whose quality and dhabi cannot be identified properly.